EVALUATION OF POLICY IMPLEMENTATION OF FREE EDUCATION ON SENIOR SECONDARY EDUCATION IN PALEMBANG CITY - Suherman, Suherman (Journal of Education Research in Administration and Management (JERAM), 2017)
The research aim is to find out policy formulation process, policy implementation; and the policy results on free education financing policy in Dompu Regency This research applied evaluation method by using Stake Countenance model The data were collected through questionnaires, interview, observation and documents. The result shown that policy formulation was based on (1) the rough enrollment rate of senior secondary education (2) the income per capita of the people Dompu; and (3) it was also supported by relevant regulations All of the steps in formulating the policy were followed as well as The policy contents contained stra tegic issues and actions, procedure, and goals or objectives The policy implementa tion process were based appropriately on method and guideline required The result of policy implementation, such as improvement of rough enrollment rate of senior secondary education was effectively achieved Before the implementation of the policy, the rough enrollment was 50,28% (2007) and it was 88,56% (2011)This per centage exceeded the national target 64,6% (2011); (2) it is decidable that the policy is responsive because since the policy is applied the parents pay nothing for the school fees; (3) the free of charge education policy implemented appropriately for all senior secondary students; (4) the policy is ineffective to the improvement teachers and staffs competencies, performance, and welfare, ineffective to the improvement students motivation and achievement, and parents participations became lower.